UPAYA GURU DALAM MENANAMKAN NILAI PENDIDIKAN KARAKTER MELALUI KEGIATAN MENDONGENG PADA ANAK USIA DINI DI TK NURUL AMIN KABUPATEN BONE - Fatimah, Nurul; Sarea, Muh. Syahrul; Syam, A. Sri Mardiyanti (EDUCHILD (Journal of Early Childhood Education), 2024)
This study aims to: 1) To determine the form of instilling character education values through storytelling activities in AUD 2) to determine teachers' efforts in instilling character education values through storytelling activities in AUD 3) To determine teachers' obstacles in instilling character education values through storytelling activities in AUD. The type of research used is descriptive qualitative with a research approach using a sociological and psychological approach. This study uses data analysis techniques with the process of reducing data, presenting data and drawing conclusions. Storytelling is one of the basic competencies in PAUD that can improve the quality and services to educators and stimulate aspects of child development through the storytelling method. The results of the study showed that there are three forms of instilling character education values through storytelling activities in AUD at Nurul Amin Kindergarten, Carigading Village, Awangpone District, Bone Regency, namely a) Religious values b) Honesty values c) Social care. Furthermore, there are teacher efforts in instilling character education values through storytelling activities in AUD at Nurul Amin Kindergarten, Carigading Village, Awangpone District, Bone Regency, namely the storytelling/storytelling method, asking children to tell fairy tales that have been heard. Furthermore, the teacher's obstacles in instilling character education values through storytelling activities in AUD at Nurul Amin Kindergarten, Carigading Village, Awangpone District, Bone Regency, namely the lack of focus from children during the learning process.